2014
DOI: 10.18632/oncotarget.2187
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability and ploidy status define three categories with distinctive prognostic impact in endometrioid endometrial cancer

Abstract: Microsatellite instability (MSI) and aneuploidy are inversely related phenomena. We tested whether ploidy status influences the clinical impact of MSI in endometrioid endometrial cancer (EEC). We analyzed 167 EECs for MSI and ploidy. Tumors were classified in three categories according to MSI and ploidy status. Associations with clinicopathological and molecular variables, survival, and treatment response were assessed.All MSI tumors (23%) were scored as diploid, and 14% of microsatellite stable (MSS) tumors p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
0
10
0
3
Order By: Relevance
“…Although dMMR has been associated with a better prognosis in CRC, its prognostic significance in EC is unclear. 21 Whereas many studies have reported worse survival and/or shorter disease-free survival among patients dMMR or microsatellite instability (MSI), 10,14,[22][23][24][25] other studies have demonstrated improved survival [26][27][28][29] or no association. [30][31][32][33] A recent meta-analysis also demonstrated no association between MMR status and OS or RFS.…”
Section: Discussionmentioning
confidence: 99%
“…Although dMMR has been associated with a better prognosis in CRC, its prognostic significance in EC is unclear. 21 Whereas many studies have reported worse survival and/or shorter disease-free survival among patients dMMR or microsatellite instability (MSI), 10,14,[22][23][24][25] other studies have demonstrated improved survival [26][27][28][29] or no association. [30][31][32][33] A recent meta-analysis also demonstrated no association between MMR status and OS or RFS.…”
Section: Discussionmentioning
confidence: 99%
“…Further on, increased Microsatellite instability (MSI) and abnormal cell cycle protein play an important role in HOTAIR oncogenic event. Diploid tumors with Microsatellite instability (MSI) have poor clinical outcome and respond worse [ 45 , 46 ]. MMR defect seems to be related with sporadic-microsatellite instability (MSI) and Cell cycle proteins abnormal expression [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…PTEN, a tumor suppressor gene has been shown to be altered in up to 83% of endometrial adenocarcinomas and 55% in precancerous lesions [45]. Microsatellite instability (MSI) has been demonstrated in 20% of type I EC [46]. According to Bilbao et al both PTEN mutations and MSI represent early events in endometrial carcinogenesis [47].…”
Section: Molecular Genetics Of Endometrial Cancermentioning
confidence: 99%